Implementação dos detectores de borda gradiente da erosão e gradiente da dilatação no software de domínio público cartomorph - Chaves, Carolina Dias [UNESP]; Da Silva, Erivaldo Antônio [UNESP] (My University, 2015)
The digital image processing is of great importance to extract information in the fields remote sensing, cartography and mathematics. The work presents the results of the gradient edge detectors erosion and dilatation implementation in CARTOMORPH software, who has been developed by the mathematical morphology group of FCT/UNESP. We used the Mathematical Morphology technique to developed this library. In order to do that, it was used the C++ language, software MATLAB, Mathematical Morphology Toolbox, satellite images of medium and high resolutions. The result demonstrate the correct implementation of operators and potential usage in the field of cartography.
Gradient edge detectors erosion and dilatation implementation in public domain CARTOMORPH software